Kompetensi Literasi Digital Mahasiswa Program Studi Pendidikan Geografi FKIP Universitas Lambung Mangkurat - Nurul Huda; Sidharta Adyatma; Karunia Puji Hastuti (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2024)
The development of science and technology (IPTEK) which is very massive has a very broad influence on all aspects of human life. One of them is education and teaching that can facilitate the exchange of information so that it is not bound by space and time. This is of course very useful, especially for students, groups who always need information as reference material for their daily assignments. Therefore, students really need information literacy skills, to support the lectures they follow. There are several models used to measure a person's literacy ability, one of which is the Empowering 8 model, where this model was produced from a workshop conducted in Sri Lanka in 2004. The purpose of this study was to analyze the digital literacy competence of students of the geography education study program, FKIP Lambung Mangkurat University. This study uses a descriptive method with a quantitative approach. Based on the results of research that has been carried out, digital digital literacy students of geography education FKIP Lambung Mangkurat University are at a good or mastered level. Where from the respondents' answers, 17% were very dominant, 71% controlled, 11% did not master, and 1% did not master. Respondents who are very mastering, not mastering, and very not mastering are in the low category, respondents who are mastering are in the high category.